Doctor Tirta’s Branding As An Influencer In The Telemedicine Program - Irawan Irawan; Lulu Nurul Azkiyah; Ardian Setio Utomo; Dewi Warhamni (Jurnal Mutakallimin : Jurnal Ilmu Komunikasi, 2023)
New media presents social media as a medium for interacting, collaborating, sharing, communicating, and forming social bonds with other users. During the COVID-19 pandemic, influencers used new media to socialize Covid-19 prevention and build personal branding. Dr. Tirta is an influencer in building personal branding with the telemedicine program he created. Telemedicine has received a lot of positive responses from the public. This research aims to determine the personal branding of Dr. Tirta as an influencer in the telemedicine program. The theory used in this research is Montoya's eight Personal Branding theories. This research uses a qualitative method with a descriptive approach. In collecting data using observation techniques, in-depth interviews with telemedicine patients, Dr. Tirta, and documentation. The research results show that Dr. Tirta has described eight personal branding concepts from Montoya. The specialty of Dr. Tirta is different from the concept of personal branding in general. Dr. Tirta does not focus on one unique skill. He has two skills, namely, in business and health. Apart from that, Dr. Tirta is an eccentric appearance characterizes, and his way of speaking seems blunt. Its consistency and determination in educating the public regarding health on social media with attractive packaging also give a positive impression.